Pelatihan Motivasi Berwirausaha Pada Survivor Bipolar di Komunitas Bipolar Care Indonesia Simpul Yogyakarta - Andhita Dyorita Khoiryasdien; Annisa Warastri (LPPM UMRI, 2020)
Bipolar disorder is a psychiatric disorder in which the sufferer has episodes of mania and depression. The difference between bipolar disorder and those who don't suffer from bipolar disorder is that people with bipolar disorder will feel sad or happy without the need for a clear reason. Bipolar survivors can still move normally under stable conditions. However, the negative community stigma of mental disorders make it difficult for bipolar survivors to find work and become unproductive. Bipolar survivors only get education related to mental health and pharmacy all this time. Bipolar survivors need education about development and empowerment. Then training is needed that provides education to bipolar survivors on motivation in entrepreneurship. The result is increased understanding of participants in managing emotions, motivation, opportunities and business innovation. In addition, participants also succeeded in preparing business plans.